The desolations of devil's acre - Riggs, Ransom (Penguin Books, 2021)
"The epic conclusion to the... Miss Peregrine's Peculiar Children series by Ransom Riggs. Jacob and his friends will face deadly enemies and race through history's most dangerous loops in this thrilling page-turner. The Desolations of Devil's Acre is the newest installment, and final adventure, in the beloved Miss Peregrine's Peculiar Children series."--Publisher's website.